Flow Experiences across Multiple Performance Domains - Mauldin, Kristin; Thompson, Bailey; Rubio, Andrea; Betancourt, Yilena; Brana, Gerardo; Hernandez, Janeane; Gonzalez, Lindsey; Batherson, Matthew; Lewin, Rachael (Advances in Social Sciences Research Journal, 2025)
As the construct of flow is currently under revision, the nine dimensions of the Jackson-Marsh Model of flow have been examined more closely. The current study aims to add to this examination by comparing these dimensions across four performance domains: academic, individual sport, spectator sport, and team sport. Participants completed two different flow assessments within one hour following their specified performance activity. One of the assessments measured state specific flow (FSS-2, Jackson & Marsh, 1996). A total of 118 performers participated: academic (n = 26), individual sport (n = 26), spectator sport (n = 32), and team sport (n = 34). Multivariate analysis of variance analyses conducted on the dimensions that represent antecedents of flow (challenge to skills match, clear goals, and unambiguous feedback) revealed less unambiguous feedback for the exam takers (academic) in comparison to the individual sport athletes, spectator sport athletes, and team sport athletes. A multivariate analysis of variance was then conducted comparing dimensions of the experience of flow between activity types. Individual sport athletes experienced higher levels of merging of action and awareness while spectator sport athletes experienced less loss of self-consciousness between the performance domains. Implications of these differences for the flow construct are discussed.